Nonpolar Solvent‐Dispersible Alkylated Reduced Graphene Oxide for Hole Transport Material in n‐i‐p Perovskite Solar Cells. Issue 4 (8th March 2021) - Park, Jong-Jin; Lee, Minwoo; Kim, Yunseul; Kim, Dong-Yu
Abstract : Reduced graphene oxides (rGOs), despite their excellent electrical properties, have been seldom used as the solution‐processed sole hole transport material (HTM) in perovskite solar cells (PeSCs) with an n‐i‐p structure, due to their low dispersity in orthogonal solvent of perovskite, such as chlorobenzene (CB). The limited rGO dispersion in nonpolar solvents precludes the formation of a fully covered film on top of the perovskite layer. A newly designed alkylated rGO (AF‐rGO) is synthesized, which can be highly dispersed in a nonpolar solvent, for use as a solution‐processed HTM on top of the perovskite layer in PeSCs. The AF‐rGO can be dispersed in CB at a high concentration, and a fully covered AF‐rGO film is successfully introduced on top of the perovskite layer as HTM through a simple solution process. The AF‐rGO in the PeSC exhibits minimal series resistance and charge recombination and exhibits efficient hole extraction and transport abilities, resulting in a maximum power conversion efficiency (PCE) of 17%, which is the highest PCE of PeSCs with an n‐i‐p structure, which use graphene‐based materials as the sole HTM. Moreover, devices with AF‐rGO HTM exhibit improved ambient stability, exhibiting 89% of their original performance after 240 h of storage without encapsulation. Abstract : The alkylated reduced graphene oxide (AF‐rGO) is well dispersed in nonpolar solvents; thus, it is successfully coated on top of the perovskite layer as a hole transport layer (HTL) through a solution process. An AF‐rGO‐based planar n‐i‐p perovskite solar cell (PeSC) shows the highest efficiency among the planar n‐i‐p PeSC using graphene materials as the sole HTL.